2010
DOI: 10.1080/10942910903034833
|View full text |Cite
|
Sign up to set email alerts
|

Grain and Food Quality Traits of Some Indigenous Medicinal Rice Cultivars of Manipur, India

Abstract: Manipur, a northeastern state of India lying in the Indo-Burmese biodiversity hot-spot is endowed with rich biodiversity of rice cultivars including those with medicinal values. The systematic evaluation of the indigenous cultivars for their grain and food qualities has not been carried out yet. Hence 13 indigenous medicinally used cultivars were subjected to grain and food quality studies. The cultivar, Naganap, has found to be of high protein type. Chinachang and Meriunap possessed strong scent comparable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…They also found these two cultivars to be nutritionally rich with high dietary fiber, protein, and minerals as compared to a popular rice cultivar, Sona Mashuri, grown in southern India. Another study that evaluated 10 aromatic rice together with three non-aromatic indigenous cultivars of Manipur for grain quality revealed that most of them possessed long bold chalky grains with high ASV and low to intermediate amylose content (Thongbam et al, 2010). Our study revealed that the landraces were low yielding, exhibited high spikelet sterility, were grain shattering, and were photo-sensitive (data not presented).…”
Section: Discussionmentioning
confidence: 63%
“…They also found these two cultivars to be nutritionally rich with high dietary fiber, protein, and minerals as compared to a popular rice cultivar, Sona Mashuri, grown in southern India. Another study that evaluated 10 aromatic rice together with three non-aromatic indigenous cultivars of Manipur for grain quality revealed that most of them possessed long bold chalky grains with high ASV and low to intermediate amylose content (Thongbam et al, 2010). Our study revealed that the landraces were low yielding, exhibited high spikelet sterility, were grain shattering, and were photo-sensitive (data not presented).…”
Section: Discussionmentioning
confidence: 63%
“…[6] The Indian rice, particularly 'basmati', receives a premium position in the market [7] due to high cooked kernel elongation with minimum breadthwise elongation, high aroma, fluffiness, palatability, and easy digestibility. Recently, genetic improvement of basmati rice varieties has led to the development of a number of high yielding and high quality traits in basmati/aromatic rice varieties (Pusa Basmati 1, Pusa Basmati 1121, Pusa Basmati 1401, Pusa Basmati 1460, Pusa Sugandh 5, and Pusa RH 10).…”
Section: Introductionmentioning
confidence: 99%
“…Significant positive correlations between length and diameter (P= 0.001) and length and shape (P= 0.001) were observed. A positive correlation of grain length with shape was reported by Wadchararat et al (2006), Thongbam et al (2010) and Rasool et al (2015). These results indicate that increased length is associated with the slender shape.…”
Section: Physical Properties Of Traditional Rice Grainsmentioning
confidence: 52%